Memetakan Pola Komunikasi Dinas Tenaga Kerja dalam Memediasi Konflik Industrial di Kabupaten Mandailing Natal - Kapsan Usman Utomo; Lahmuddin Lahmuddin; Mailin Mailin (Program Studi Ilmu Komunikasi, 2023)
This study aimed to describe the Islamic communication model of the Labour Agency in mediating industrial relation conflicts between employers and labourers in Mandailing Natal District. This study used a qualitative descriptive method. The results of this study indicated that the Labour Agency used Islamic communication model in mediating the Industrial relation conflicts. This study discovered that the role of interpersonal religious communication from the mediators to solve the disputes between the labourers and employers of Mandailing Natal Labor Agency was very crucial. In this case, interpersonal communication through dakwah was highly useful in formulating solutions that could be accepted by both conflicting sides without causing further conflicts. Islamic communication models should be investigated further in order to complement the Western communication theory in solving labour disputes such as in Mandailing Natal.